Facile synthesis of zirconium-organic frameworks@biomass-derived porous graphitic nanocomposites: Arsenic adsorption performance and mechanism - Pandi, Kalimuthu; Lee, Da-won; Choi, Jaeyoung (ELSEVIER, 2020)
This work describes the preparation of novel adsorbents based on a natural biomass-derived porous graphic carbon (PGC) as a backbone for the interfacial growth of zirconium-organic framework (UiO-66) using an in situ synthetic route for the adsorption of total arsenic from water. The pristine UiO-66 and their PGC loaded nanocomposites (UiO-66@PGCx%, where x = (5, 10, 20, and 50) % (wt/wt), were tested for the adsorption of As (III)/As(V) and batch adsorption results show that the UiO-66@PGC20% nanocomposite achieves superior removal efficiencies for As(III)/As(V), compared with other developed nanocomposites and pristine UiO-66. The developed adsorbents are highly pH dependent and selective in common co-existing anions except for F-, PO43- and humic acid. The adsorption data was fitted using Langmuir isotherm and pseudo-second-order kinetic models. The adsorption mechanism was revealed through FTIR and XPS analysis, and the chemisorption of As(III)/As(V) on the surface of the UiO-66@PGC20% nanocomposite was explored. The UiO-66@PGC20% nanocomposite exhibits better chemical stability under the adsorption-desorption process and similar to 500 and 651 bed volumes of As(III)/As(V) contaminated water were treated in continuous fixed-bed column, also reduced the As(III)/As(V) concentration to <10 mu g/L, which indicates that the UiO-66@PGC20% nanocomposite is a practical adsorbent in the field of arsenic remediation. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: HYDROTHERMAL CARBONIZATION; EFFICIENT REMOVAL; CARBON MATERIALS; UIO-66; WATER; SURFACE; WASTE; SUPERCAPACITOR; COMPOSITES; MEMBRANES